2019
DOI: 10.3390/jmse7100332
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Observations of Turbulent Events in the Surfzone

Abstract: In coastal dynamics, large-scale eddies transport and spread smaller turbulent vortices both towards the sea surface, thus contributing to the processes of air-water gas transfer, and towards the sea bottom, inducing sediment pick-up and resuspension. The mechanical role of the breaking-induced vortices to the redistribution of turbulence and turbulent kinetic energy is still unclear and needs a more thorough study, possibly supported by more measurements in this field. Based on this, the present paper aims to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Closer inspection shows that a phase-lead occurred between k and u; k ramped up prior to velocity maxima and was followed almost instantly by sharply defined puffs of suspended sediment. The general signatures shown in Figure 15 echo several reports [71,73,100] that point to the fact that for plunging waves, k-arrival at the seabed typically occurs under the front face, or at the crest of the waves (the relative timing probably depending on water depth (h) and the turbulent length scale (l)). For spilling breakers, however, TKE moves more slowly downward and typically arrives either on the back of the wave crest [86] (see also Figure 4), or as late as the on/offshore velocity reversal [100].…”
Section: Intra-wave Properties Of Turbulence and Sediment Suspensionsupporting
confidence: 78%
See 1 more Smart Citation
“…Closer inspection shows that a phase-lead occurred between k and u; k ramped up prior to velocity maxima and was followed almost instantly by sharply defined puffs of suspended sediment. The general signatures shown in Figure 15 echo several reports [71,73,100] that point to the fact that for plunging waves, k-arrival at the seabed typically occurs under the front face, or at the crest of the waves (the relative timing probably depending on water depth (h) and the turbulent length scale (l)). For spilling breakers, however, TKE moves more slowly downward and typically arrives either on the back of the wave crest [86] (see also Figure 4), or as late as the on/offshore velocity reversal [100].…”
Section: Intra-wave Properties Of Turbulence and Sediment Suspensionsupporting
confidence: 78%
“…locity [69] which may sometimes produce scour holes on the seabed [70]. In the field, Aa-gaard and Hughes [28] observed instantaneous velocities up to w ≈ 1 ms −1 at an elevation 15 cm above the bed, and wrms was about a factor 2 larger for plunging compared to spilling breakers of the same height, while deSerio and Mossa [71] reported that u' was a factor 3 larger for plunging compared to spilling breakers.…”
Section: Turbulence Generation Spatial Structure and Magnitudementioning
confidence: 99%
“…Many laboratory experiments have been conducted to study the surf and swash flow induced by periodic waves. The typical phase-averaging method is applied to the time series of velocity measurements in a single experimental run so as to obtain the turbulent velocities based on the Reynolds decomposition concept (Ting & Kirby 1995Cox & Kobayashi 2000;Petti & Longo 2001;Cowen et al 2003;De Serio & Mossa 2006;Kimmoun & Branger 2007;Sou, Cowen & Liu 2010;Sou & Yeh 2011;De Serio & Mossa 2019), the resulting turbulent intensities are likely overestimated if the wave record in a single run is not perfectly periodic and the errors are difficult to estimate (Sou et al 2010). Moreover, if the wavemaker is not able to absorb all the reflected waves from the beach, the waves in the wave flume are no longer pure progressive waves, making the interpretation of the resulting wave-wave interactions in the swash flows difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies evaluated the integral length scale in various ways, e.g. Ting & Kirby (1996), Petti & Longo (2001), Govender et al (2004), De Serio & Mossa (2019) and Sou et al (2010). One of the methods to estimate the integral length scale is to use the scaling relationship between the dissipation rate and the turbulent kinetic energy k as L = c d k 3/2 / , in which c d is an empirical coefficient (Govender et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental simulations [1][2][3] and numerical simulations [4][5][6][7][8][9][10][11][12] of hydrodynamic fields, turbulent phenomena and concentration of suspended sediment under breaking waves allow for the analysis of the effects produced by wave motion and coastal structures on the bottom and coastline modifications. In numerical simulations, the definition of the turbulent closure relations under breaking waves is one of the most important issues to adequately represent the three-dimensional velocity fields and the turbulent phenomena that develop near the bottom boundary.…”
Section: Introductionmentioning
confidence: 99%